2021
DOI: 10.3389/fmicb.2021.783563
|View full text |Cite
|
Sign up to set email alerts
|

Coupling Root Diameter With Rooting Depth to Reveal the Heterogeneous Assembly of Root-Associated Bacterial Communities in Soybean

Abstract: Root diameter and rooting depth lead to morphological and architectural heterogeneity of plant roots; however, little is known about their effects on root-associated microbial communities. Bacterial community assembly was explored across 156 samples from three rhizocompartments (the rhizosphere, rhizoplane, and endosphere) for different diameters (0.0–0.5 mm, 0.5–1.0 mm, 1.0–2.0 mm, and>2.0 mm) and depths (0–5 cm, 5–10 cm, 10–15 cm, and 15–20 cm) of soybean [Glycine max (L.) Merrill] root systems. The m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 77 publications
(93 reference statements)
0
8
0
Order By: Relevance
“…Other studies have shown that host selection pressure increased sequentially from soils to epiphytes to endophytes, reducing bacterial diversity and network complexity ( 62 ), resulting in differentiation of the structure and function of microbial communities between the endospheric layer and rhizospheric soil. Other studies have documented the hierarchical enrichment of the bacterial community from the rhizosphere to the rhizoplane to the endosphere in soybean ( 63 ). In addition, it has been reported that some PGPR epiphytes tend to form biofilms within an extracellular matrix, the roots provide a favorable attachment environment, and root-secreted organic acids can recruit beneficial soil bacteria ( 64 ), which may contribute to the augmented effects of these PGPR in the endospheric layer of soybean.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown that host selection pressure increased sequentially from soils to epiphytes to endophytes, reducing bacterial diversity and network complexity ( 62 ), resulting in differentiation of the structure and function of microbial communities between the endospheric layer and rhizospheric soil. Other studies have documented the hierarchical enrichment of the bacterial community from the rhizosphere to the rhizoplane to the endosphere in soybean ( 63 ). In addition, it has been reported that some PGPR epiphytes tend to form biofilms within an extracellular matrix, the roots provide a favorable attachment environment, and root-secreted organic acids can recruit beneficial soil bacteria ( 64 ), which may contribute to the augmented effects of these PGPR in the endospheric layer of soybean.…”
Section: Discussionmentioning
confidence: 99%
“…In this scenario, it is possible that smaller pores act as isolated habitat patches, which can influence competitive interactions and strengthen patterns of coexistence among microbial taxa (Lowery and Ursell, 2019). This is corroborated by the fact that finer roots have been shown to contain more diverse microbial communities when compared to higher-order roots (Saleem et al, 2016;Pervaiz et al, 2020;King et al, 2021;Luo et al, 2021). Moreover, some microbial taxa have also been shown be more abundant in specific root orders (Wang et al, 2017), possibly due to their ability to compete in distinct habitat patch sizes with characteristic biotic and abiotic conditions.…”
Section: Root Branchingmentioning
confidence: 82%
“…However, ZZ6 displayed a more pronounced response to drought compared to ZZ1, which aligns with previous findings ( 23 ). The interaction between the Chao1 index of ZZ6 and root traits under drought stress highlights the influence of environmental changes and host plants on rhizosphere bacteria ( 47 , 48 ). Prolonged drought conditions cause changes in the rhizosphere-associated bacterial community structure in combinations selected to adapt to abiotic stresses, improve plant root phenotypes, and thereby increase stress resistance to promote plant health and drought tolerance ( 47 , 49 ).…”
Section: Discussionmentioning
confidence: 99%
“…Prolonged drought conditions cause changes in the rhizosphere-associated bacterial community structure in combinations selected to adapt to abiotic stresses, improve plant root phenotypes, and thereby increase stress resistance to promote plant health and drought tolerance ( 47 , 49 ). Additionally, soil properties can impact root traits by influencing nutrient and water availability, leading to variations in bacterial communities associated with the root system ( 48 ). β-Diversity analysis revealed distinct rhizosphere bacterial community compositions for ZZ1 and ZZ6 under different drought levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation